Análisis de las estrategias comunicacionales utilizadas por la empresa de soluciones gráficas Rugall en la ciudad de Guayaquil durante el año 2014 - Drouet Fiallos, Silvia Denisse (2016)
This research is based on the demonstration of the importance of using advertising in the development of PYMES. The character of this study is the graphic solutions company Rugall, extensive experience Guayaquileña company identified as one of the pioneers in the market in which it operates is. Although it is a small business, they have clear mission and vision, also has a comprehensive portfolio of services, a characteristic that distinguishes between competence. Despite the potential of this company, several factors such as ignorance, lack of professional advice or simply to avoid "expenses", it has not been given the relative importance to the management of advertising, likewise the benefits it represents for the overall development of the company. General purpose of this study is to determine the effectiveness of the communication tools used by Rugall during 2014…..